Teaching Concepts of Acoustical Waves in Air - Part 3 Reverberation - Gastmeier, Bill (Canadian Acoustics, 2024)
Teaching Concepts of Acoustics in Air - Part 3, Reverberation Bill Gastmeier, MASc PEng HGC Engineering 2000 Argentia Road, Plaza 1, Suite 203 Mississauga, Ontario, L5N 1P7 www.hgcengineering.com bgastmeier@hgcengineering.com This paper has been written to participate in the “Education in Acoustics” session at the 2024 joint conference of the Canadian Acoustical Association and the Acoustical Society of America. It is written to build on Parts 1 and 2 of this series and similarly contains materials extracted from 30 years of teaching to Architects at the University of Waterloo and Dalhousie University in Halifax. The purpose of this session is to provide teachers with practical demonstrations which can be used to enhance learning of specifically the concept of Reverberation. It uses “hands on” demonstrations including physical experimentation, an audio demonstration and written materials to advance the concept. Part 1 dealt primarily with sound propagation in air and the concepts of longitudinal wave motion, speed, frequency and wavelength and related effects which relate to what we perceive as pitch. Part 2 expanded on those concepts by discussing superposition and the definition and measurement of sound pressure, decibels and the decibel scale and how to manage decibels, all of which we perceive as loudness. Part 3 deals with reverberation, which is arguably the most important aspect of how sound propagates in indoor spaces. It affects both our ability to communicate and how we experience and perceive the quality of the acoustical environment. Practical demonstrations are provided to enhance learning of the concept of Reverberation. These include “hands on” demonstrations including physical experimentation, an audio demonstration and written materials to advance the concept.